Measure learning effectiveness among children using EEG device and mobile application - Magrizef Gasah; Aslina Baharum; Nurul Hidayah Mat Zain (Institute of Advanced Engineering and Science, 2020)
This paper presents a method in measuring the learning effectiveness among children using EEG device and Mobile Application. In this study, an approach to measure the children learning effectiveness using a mobile learning application and EEG device have been developed. The method used to develop the approach was from the extensive literature review from previous research related to children learning effectiveness and its experimental works. A quantitative method was used to measure the effectiveness of children learning and the result of this experimental work shows that children learning effectiveness can reach nearly 73%. Since lot of teachers and student having trouble in accessing the learning activity whether it was effective or not, this study shown a significant way to solve such problem.